Beckman O2 Partial Pressure Transducer - Dietrich, T. A. (1965)
The oxygen transducer monitored a monkey's air supply on a 30 day Biosatellite Program mission.
Keywords: Transducers; Scientific apparatus and instruments; Oxygen--Measurement; Electronics in space medicine; Beckman Instruments, Inc.